The European Semester and Parliamentary Oversight Institutions Inside and Outside of the Euro Area - Winzen, Thomas (2021)
The European Semester is a challenge for national parliaments but also an opportunity to reform domestic oversight institutions. Drawing on data from all member states, this study examines the conditions under which national parliaments use this opportunity. Is Euro area membership a prerequisite for parliamentary adaptation to the European Semester and, if so, which further combinations of conditions account for variation among Euro area countries? The analysis suggests that membership in or close ties with the Euro area and institutional strength constitute necessary conditions for parliamentary adaptation. Combined with other factors—in particular, public debt exceeding the Maastricht criteria—these conditions explain reform in many cases. National parliamentary adaptation to the European Semester thus follows existing institutional divisions constituted by differentiated integration in the Euro area and uneven national parliamentary strength.